Cоотношение мотивационных факторов и уровня креативности в профессиональном развитии работников библиотек (Библиосфера, 2010)
This article discloses the correlation between activity motivation and behavior of the library staff, describes the theories of professional education, the models of adaptive behavior, the levels of creative ability development.